PENGARUH PENGGUNAAN TEKNIK TIRU MODEL TERHADAP KETERAMPILAN MENULIS TEKS PUISI SISWA KELAS X SMAN 4 PADANG - Harmooni, Monicha Fuji; R.,, Syahrul; Basri, Irfani (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACT This article was written to illustrate the effect of using model Copy The Master techniques on the writing skills of poetry text in class X of SMA Negeri 4 Padang. This research used quantitative method which usedone group pretest and posttest design. The population of this research in class X of SMA Negeri 4 Padang. There was 288 population but there was only one class to be the sampel. It was class X MIPA 1 which consisted of 32 students that choosen by using purposive sampling technique. Research data is the result of the score in the skill of writing poetry text before and after using model Copy The Master technique. This study has three result. First, the skill to write poetry text in class X of SMA Negeri 4 Padang before using the model Copy The Master technique with an average score of 69,27. Second, the skill of writing poetry text of the students of class X SMA Negeri 4 Padang aftel using the model imitation technique with an average score of 79,39. Third, based on the t-test at the level of 0.95 obtained tcount >ttabel (4,62> 1,70). So, it can be said that H1 is accepted. This means that there can be a significant influence on the use of model Copy The Master techniques on the writing skills of poetry text in class X of SMA Negeri 4 Padang. Kata Kunci: Pengaruh, Teknik Copy The Master, Kemampuan Menulis, Teks         Puisi